Does Tax Avoidance Make Do Earning Opacity? - Andi Arman; Mira Mira (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
This study examines and analyzes the effect of earning opacity on tax avoidance with leverage and company size as control variables in manufacturing companies listed on the Indonesia Stock Exchange. This research is quantitative research with an approach explanatory research involving 42 companies from 187 companies engaged in the manufacturing sector listed on the Indonesia Stock Exchange in 2017-2019. Determination of the sample using a purposive sampling technique. The data in this study were collected using literature study and documentation study methods. Furthermore, the data were analyzed using descriptive statistical methods, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test), multiple linear regression, determination test, and hypothesis test (t-test). The results showed that earning opacity hurts tax avoidance and is proven to be significant. This is because the company is less likely to minimize the tax burden. After all, the company no longer needs to carry out or take advantage of existing tax regulatory loopholes to minimize tax burden because its profit information has been obscured by management. Furthermore, the earning opacity carried out by company management is behavior opportunistic to maximize individual profits so that it is believed that there is less tax avoidance. This is because tax avoidance is done for the benefit of the company.